Reliability and Fault Analysis of a Stochastic Model of a Standby System with Cost Depended Repair/Replacement of Substandard Unit and Correlated Life Time - Sarita; Bhatia, P.; Kumar, S.; Dhingra, H. K. (Journal of Scientific Research, 2022)
The present paper deals with the reliability and fault analysis of a stochastic model for two non-identical units, in which the first unit is kept as operative and the other sub-standard one. The sub-standard unit may be repaired or may be replaced by another sub-standard unit on its failure, depending on the cost of repairing/replacement. Failure and repair times are considered correlated using bivariate point exponential distribution. Analysis of a system is done to find various reliability measures, which gives the system's effectiveness. The conclusion about these reliability measures is carried out by graphical studies. The main emphasis is on the correlation between repair time and failure time.